2009
DOI: 10.1038/leu.2008.349
|View full text |Cite
|
Sign up to set email alerts
|

Repression of Gadd45α by activated FLT3 and GM-CSF receptor mutants contributes to growth, survival and blocked differentiation

Abstract: The tumor suppressor Gadd45a was earlier shown to be a repressed target of sustained receptor-mediated ERK1/2 signaling. We have identified Gadd45a as a downregulated gene in response to constitutive signaling from two FLT3 mutants (FLT3-ITD and FLT3-TKD) commonly found in AML, and a leukemogenic GM-CSF receptor trans-membrane mutant (GMR-V449E). GADD45A mRNA downregulation is also associated with FLT3-ITD þ AML. Sustained ERK1/2 signaling contributes significantly to receptor-mediated downregulation of Gadd45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 49 publications
3
18
0
Order By: Relevance
“…To examine whether the impaired colony-forming ability of 32D-RUNX1dC cells attributed to the repressed expression of Gadd45a by RUNX1dC, we introduced the expression vector for Gadd45a into 32D-RUNX1dC cells, which was named 32D-RUNX1dC-Gadd45a (Supplementary Figure 3a). Consistent with the report from Perugini et al, 27 Gadd45a overexpression reduced the cell proliferation ability at steady state (Figure 4a Figure 3b). Furthermore, we found exogenously expressed Gadd45a reduced gH2AX-positive foci in 32D-RUNX1dC-Gadd45a cl1 cells compared with 32D-RUNX1dC-GFP cells after UV-B treatment (Figure 4b).…”
Section: Runx1dc Suppresses Gadd45a Expression In Lsk Cellssupporting
confidence: 82%
See 1 more Smart Citation
“…To examine whether the impaired colony-forming ability of 32D-RUNX1dC cells attributed to the repressed expression of Gadd45a by RUNX1dC, we introduced the expression vector for Gadd45a into 32D-RUNX1dC cells, which was named 32D-RUNX1dC-Gadd45a (Supplementary Figure 3a). Consistent with the report from Perugini et al, 27 Gadd45a overexpression reduced the cell proliferation ability at steady state (Figure 4a Figure 3b). Furthermore, we found exogenously expressed Gadd45a reduced gH2AX-positive foci in 32D-RUNX1dC-Gadd45a cl1 cells compared with 32D-RUNX1dC-GFP cells after UV-B treatment (Figure 4b).…”
Section: Runx1dc Suppresses Gadd45a Expression In Lsk Cellssupporting
confidence: 82%
“…31 The similar phenotypes of Gadd45a þ /À and RUNX1 þ /À mice raise the possibility that both molecules have closely related roles in maintaining genome stability. As for the relationship between RUNX1 and Gadd45a, Perugini et al 27 recently reported that GADD45A expression was significantly downregulated in RUNX1-ETO-positive AML cells compared with normal controls. Although they demonstrated ERK1/2 signaling was involved in the repression of GADD45A in several AML cell lines, its mechanism was not analyzed in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Gadd45a was primarily considered as a pro-apoptotic gene, and has been reported as being able to activate the mitochondrial pathway of apoptosis [26] . It has been reported that knockdown of Gadd45a led to increased growth and survival of FDB1 myeloid cells [27] . Moreover, Zhang et al found that high level expression of Gadd45a sensitized M1 myeloblastic leukemia and H1299 lung carcinoma cell lines to apoptosis induced by gamma-irradiation [28] .…”
Section: Discussionmentioning
confidence: 99%
“…TC252 GADD45A-overexpressing cells were generated using retroviral spin-infection as previously described (21).…”
Section: Gadd45a Overexpressionmentioning
confidence: 99%